Self-prestressing bonded patches using Fe-SMA and CFRP for lifetime extension of fatigue-cracked steel details - Wang, Sizhe (2024)
Self-prestressing bonded patches employing iron-based shape memory alloy (Fe-SMA) and carbon fiber reinforced polymer (CFRP) for lifetime extension of cracked steel structures are investigated. The repair patches, applicable in confined spaces, are bonded over cracks, with prestress generated within Fe-SMA via activation (heating and cooling) to induce compression on cracks. Experimental tests involve cracked steel plates repaired with Fe-SMA and Fe-SMA/CFRP bonded patches, with a patch width of 50 mm and varied patch lengths of 100[sbnd]500 mm. Fe-SMA strips are activated to 180 ℃ using electric heating, generating prestresses of 154[sbnd]254 MPa. Fatigue tests (∆σ=90 MPa, R=0.2) show fatigue life extensions of ≥4.2 and ≥5.5 times for Fe-SMA and Fe-SMA/CFRP repairs. The 100 mm long Fe-SMA/CFRP patch exhibits optimal performance in lifetime extension, achieving complete crack arrest. As patch lengths decrease, failure modes shift from Fe-SMA (and CFRP) fracture to patch debonding while all patches remain effective in fatigue life extension. Finite element analysis with experimental validation quantifies the effects of prestress and load-sharing on reducing stress intensity factors at crack tips, thus retarding crack propagation. Design recommendations are proposed for the application of self-prestressing patches.